Pemanfaatan Buah Pepaya Menjadi Keripik Dan Digitalisasi Marketing Di Desa Lelede Kecamatan Kediri Kabupaten Lombok Barat NTB - Hj. Erviva Fariantin; Rusdi; Syaiful Amri; Indah Ariffianti; Elvina Setiawati; Sopian Saori; Dedy Febry Rachman (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi AMM, 2024)
The aim of this service is to utilize papaya fruit to make papaya chips and digitize marketing in Lelede Village, Kediri District, West Lombok Regency, NTB. We know that papaya can not only be consumed directly but can also be processed into various foods, one of which is